Meningkatkan Hasil Belajar Materi Aritmetika Sosial Melalui Model Pembelajaran Teams Games Tournament - Sri Hariyani; Oni Lemba Kamunggul (IKIP Mataram, 2019)
Improving Students' Learning Outcomes on Social Arithmetic Material Through Teams Games Tournament Learning Model. This study aims to describe the TGT learning steps that can improve the learning outcomes of social arithmetic material in class VII of PGRI 01 Singosari Middle School. This research is qualitative research with a type of classroom action research (CAR). Data sources were students of class VII D SMP PGRI 01 Singosari as many as 27 students. The procedure for collecting data in this study are (1) Observation, (2) Tests, and (3) Documentation. Stages of data analysis include reducing data, presenting data, and drawing conclusions. Examination of the validity of the data used includes (1) persistence of observation, (2) triangulation, and (3) peer examination. The results of the study showed an increase in teacher and student activity from pre-action to action I and action II. The observation results of teacher activities in action I reached a percentage of 86.23%, in action II, it increased to 95.45% with a very good category. Furthermore, the observation results of student activities in action I reached a percentage of 79.3% and in action II, it increased to 91.73%. The percentage of completeness of student learning outcomes in pre-action was 40.74%, the percentage of completeness of action I was 66.67%, and the percentage of completeness of action II was 85.18%. Thus the increase in learning outcomes from the action I to action II is 18.51%.